2011
DOI: 10.1063/1.3579397
|View full text |Cite
|
Sign up to set email alerts
|

Large acoustic solitons and double layers in plasmas with two positive ion species

Abstract: Large nonlinear acoustic waves are discussed in a plasma made up of cold supersonic and adiabatic subsonic positive ions, in the presence of hot isothermal electrons, with the help of Sagdeev pseudopotential theory. In this model, no solitons are found at the acoustic speed, and no compositional parameter ranges exist where solutions of opposite polarities can coexist. All nonlinear modes are thus super-acoustic, but polarity changes are possible. The upper limits on admissible structure velocities come from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Clearly, the plasma composition parameter values that give rise to the switch are critical [10,24,29], and in this model one is led to critical values of the nonthermality parameter, β c , and dust charge fraction, denoted by f c . It is possible with this technique to find numerous realistic plasma models in which, for some fixed plasma parameter values, both polarities are supported [4,10,14,17,24,28,31,32], a phenomenon sometimes referred to as "coexistence" [24,[28][29][30][32][33][34]. Even though positive and negative solitons can occur for the same parameter values in the Sagdeev pseudopotential, only one possibility can be realized at a time, depending on the initial perturbations.…”
Section: Basic Formalismmentioning
confidence: 99%
“…Clearly, the plasma composition parameter values that give rise to the switch are critical [10,24,29], and in this model one is led to critical values of the nonthermality parameter, β c , and dust charge fraction, denoted by f c . It is possible with this technique to find numerous realistic plasma models in which, for some fixed plasma parameter values, both polarities are supported [4,10,14,17,24,28,31,32], a phenomenon sometimes referred to as "coexistence" [24,[28][29][30][32][33][34]. Even though positive and negative solitons can occur for the same parameter values in the Sagdeev pseudopotential, only one possibility can be realized at a time, depending on the initial perturbations.…”
Section: Basic Formalismmentioning
confidence: 99%
“…49,54,56 As mentioned above, KdV theory can only yield solitons of one polarity for a given composition, and its polarity coincides with the sign of the coefficient of the nonlinear KdV term. 43,49,56 Further, it was shown that the sign of the latter KdV coefficient can be found from the Sagdeev potential through that of S 000 ð0; M s Þ. 43,49 On the other hand, the "other" soliton was found to have finite amplitude at the acoustic speed, i.e., it was clearly "nonKdV-like" in behavior.…”
Section: Introductionmentioning
confidence: 90%
“…40 The true acoustic speed, M s , is found from the Sagdeev potential through S 00 ð0; M s Þ ¼ 0, where primes denote differentiation with respect to u. 49,54,56 As mentioned above, KdV theory can only yield solitons of one polarity for a given composition, and its polarity coincides with the sign of the coefficient of the nonlinear KdV term. 43,49,56 Further, it was shown that the sign of the latter KdV coefficient can be found from the Sagdeev potential through that of S 000 ð0; M s Þ.…”
Section: Introductionmentioning
confidence: 99%
“…The converse, however, is certainly not true: one can have polarity changes and double layers without coexistence. 61,62 However, all possible ramifications of a precise link between polarity changes and coexistence domains have not been exhaustively investigated yet.…”
Section: Polarity Switches and Coexistence Domainsmentioning
confidence: 99%